Temperature Evolution of Charge Carrier Density in the Centre of the Brillouin Zone of Fe(Se,Te) Superconductor - Pustovit, Yu.V.; Brouet, V.; Chareev, D.A.; Kordyuk, O.A. (Металлофизика и новейшие технологии, 2018)
A characteristic feature of the electronic structure of iron-based superconductors is the shift of experimental electronic bands in comparison to the results of calculations. The temperature dependence of the band structure for FeSe can manifest the mechanism of such shifts, but different studies give opposite directions for these shifts in the centre of the Brillouin zone. In this paper, we report downward shift of both dxz and dyz bands in Z point within the temperature range 20–160 K. Together with the results of evolution of the electronic structure in A point, such shifts should lead to a break of parity between electron and hole charge carriers that can be interpreted as an increase of electron-carrier density with increasing temperature.